PARALLELS IN LEXICAL DERIVATION BETWEEN THE ENGLISH AND UZBEK LANGUAGES AS OBSERVED WITHIN THE TEXT (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article investigates the similarities in lexical derivation between English and Uzbek. Using a comparative approach, it seeks to identify commonalities in word formation across the two languages. The study examines linguistic phenomena like affixation, compounding, and borrowing to reveal shared patterns in word creation. It aims to illuminate how language structures are interconnected and how cultural and historical factors influence lexical derivation in both English and Uzbek.